Robot‐assisted kidney transplantation is a safe alternative approach for morbidly obese patients with end‐stage renal disease. Issue 5 (15th June 2021) - Lee, Seung Duk; Rawashdeh, Badi; McCracken, Emily K. E.; Cantrell, Leigh A.; Kharwat, Bassel; Demirag, Alp; Agarwal, Avinash; Brayman, Kenneth L.; Pelletier, Shawn J.; Goldaracena, Nicolas; Fox, Emily; Oberholzer, José
Abstract: Background: Many centres deny obese patients with a body mass index (BMI) >35 access to kidney transplantation due to increased intraoperative and postoperative complications. Methods: From August 2017 to December 2019, 73 consecutive cases of kidney transplantation in morbidly obese patients were enrolled at a single university at the initiation of a robotic transplant surgery program. Outcomes of patients who underwent robotic assisted kidney transplant (RAKT) were compared to frequency‐matched patients undergoing open kidney transplant (OKT). Results: A total of 24 morbidly obese patients successfully underwent RAKT, and 49 obese patients received an OKT. The RAKT group developed fewer surgical site infections (SSI) than the OKT group. Graft function, creatinine, and glomerular filtration rate (GFR) were similar between groups 1 year after surgery. Graft and patient survival were 100% for both groups. Conclusions: RAKT offers a safe alternative for morbidly obese patients, who may otherwise be denied access to OKT.